2019
DOI: 10.1016/j.neuropharm.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of agonist efficacy in exposure-induced enhancement of mu opioid reward in rats

Abstract: The abuse potential of opioid analgesics in humans appears to increase rapidly during initial regimens of opioid exposure. Previous work using intracranial self-stimulation (ICSS), a preclinical procedure useful for studying rewarding drug effects in drug-naïve animals, has similarly shown that rewarding effects of mu opioid receptor (MOR) agonists increase rapidly in rats during initial regimens of opioid administration. The goal of the present study was to evaluate the role of MOR agonist efficacy as a deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The current study showed that CP55940 produced dose-dependent depression of ICSS in rats. Similar results have been previously reported in mice and rats [44,45]. In addition, other CB1 agonists produced similar effects in ICSS such as Δ9-tetrahydrocannabinol and WIN55,212-2 ((R)-(+)-[2,3-Dihydro-5-methyl-3-(4-morpholinylmethyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1-naphthalenylmethanone mesylate) [31,46].…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that CP55940 produced dose-dependent depression of ICSS in rats. Similar results have been previously reported in mice and rats [44,45]. In addition, other CB1 agonists produced similar effects in ICSS such as Δ9-tetrahydrocannabinol and WIN55,212-2 ((R)-(+)-[2,3-Dihydro-5-methyl-3-(4-morpholinylmethyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1-naphthalenylmethanone mesylate) [31,46].…”
Section: Discussionsupporting
confidence: 92%
“…This study evaluated the abuse-related effects of tramadol in rats using an ICSS procedure that has been used to evaluate a range of other opioid analgesics (Altarifi et al, 2017; Altarifi et al, 2012; Altarifi and Negus, 2011; Altarifi et al, 2015; Moerke and Negus, 2019; Wiebelhaus et al, 2016). We have shown previously that many MOR agonists produce little or no evidence of abuse-related ICSS facilitation in opioid-naïve adult male Sprague–Dawley rats, and instead produce primarily only an efficacy-dependent ICSS depression.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were trained under a fixed-ratio 1 (FR 1) schedule of brain stimulation using procedures similar to those described previously (Altarifi et al, 2017; Altarifi et al, 2013; Altarifi et al, 2015; Moerke and Negus, 2019). Each lever press resulted in the delivery of a 0.5-second train of square-wave cathodal pulses (0.1 ms pulse duration), and stimulation was accompanied by illumination of the stimulus lights above the lever.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations